Effectiveness of Sofpironium Bromide in Patients with Primary Axillary Hyperhidrosis Who Experienced Residual or Recurrence of Axillary Odor after Surgery for Axillary Osmidrosis - Masanobu Sakisaka; Akihiko Takushima (Journal of Plastic and Reconstructive Surgery)
Objectives: Sofpironium bromide is the first topical anticholinergic drug approved in Japan for the treatment of primary axillary hyperhidrosis. This study aimed to investigate the effectiveness of sofpironium bromide in patients with primary axillary hyperhidrosis who experienced residual axillary odor or recurrence of axillary odor after surgery with subdermal excision of apocrine glands by skin flap procedure for axillary osmidrosis. Methods: A total of 56 patients who underwent surgery for axillary osmidrosis at our hospital between January 2022 and April 2023 were included in this study. Axillary odor and sweat volume were evaluated with patient-reported visual analog scale in 56 patients who underwent surgery for axillary osmidrosis and 13 patients administered with sofpironium bromide after the surgery. Results: Surgery in patients with axillary osmidrosis significantly improved axillary odor and excessive sweating by approximately 90% and approximately 54%, respectively. Treatment with sofpironium bromide in patients with axillary hyperhidrosis after the surgery significantly improved axillary odor and excessive sweating by approximately 70% and approximately 63%, respectively. Conclusions: These results suggest that sofpironium bromide is effective in patients with axillary hyperhidrosis after the surgery. Since this study was conducted with a small number of patients in a retrospective single-arm design, it is necessary to validate the results in a prospective controlled study with a large number of patients.